Elasticity, an often-overseen parameter in the development of nanoscale drug delivery systems - Weiss, Agnes-Valencia; Schneider, Marc (Beilstein Journal of Nanotechnology, 2023)
Nanoparticles have shown an enormous potential as drug delivery systems in the lab. However, translation to the clinics or even market approval often fails. So far, the reason for this discrepancy is manifold. Physicochemical properties such as size, surface potential, and surface chemistry are in focus of research for many years. Other equally important parameters, influencing whether a successful drug delivery can be achieved, are mechanical properties of nanoparticles. Even though this is often not even considered during formulation development, and it is not requested for approval, an increasing number of studies show that it is important to have knowledge about these characteristics. In this article, we discuss examples highlighting the influence of elasticity in nanoscale biological interactions focusing on mucosal delivery and on tumor targeting. Besides this, we discuss the influence of different measurement settings using atomic force microscopy for the determination of mechanical properties of drug carriers.
Keywords: atomic force microscopy; drug delivery; elasticity; mechanical properties; nanomedicine; nanoparticles; stiffness measurement; tissue/body distribution